PENYELESAIAN SENGKETA MELALUI MEDIASI OLEH PARA PIHAK DI PENGADILAN NEGERI DENPASAR DALAM PERKARA PERDATA - DIAN NINGRUMI, I GUSTI AYU; RAI ASMARAPUTRA, DEWA NYOMAN; A. MARTANA, NYOMAN (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012), 2012)
Mediation means a dispute solution by tranquility. Mediation Agreement means an agreement concluded by the parties to submit all or certain disputes which have arisen or which may arise between themto be mediated by mediator. Each party shall cooperate in good faith with the mediator to advance the mediation as expeditiously as possible.
Keywords: Mediation, Dispute, Neutral third party, Effective Law